Analisis Dalalah Lafdziyyah Dalam Surat An-Nur Ayat 2: Implikasi Hukum Islam Terhadap Fenomena Kohabitasi - Ahmad Warid Wajdil Haq; Diah Nuraini (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This research examines dalalah lafdziyah, or the study of meaning based on textual wording, in Surah An-Nur (24:2) concerning cohabitation and friends with benefits (FWB) cases. Using a case study method with an analytical-interpretive approach, this study systematically analyzes the content and textual interpretation of the verse to construct a comprehensive understanding of its meaning and implications. Findings reveal that the dalalah lafdziyah in Surah An-Nur (24:2) explicitly prohibits adultery (zina), reinforcing the Quranic stance against sexual relations outside of marriage. This prohibition extends to modern phenomena such as cohabitation and FWB, where individuals engage in intimate relationships without legal or religious marital bonds. The verse instructs unmarried individuals to avoid acts leading to adultery, emphasizing that sexual relations require a lawful framework. This study contributes to contemporary discussions on the intersection of Islamic law and evolving social behaviors, highlighting how Quranic principles remain relevant in addressing modern moral and legal dilemmas. The findings underscore the necessity for enhanced legal and educational interventions to promote awareness of Islamic ethics regarding relationships. Additionally, the research provides a critical reference for Islamic scholars, policymakers, and educators in framing responses to shifting societal norms while maintaining religious integrity. By offering a nuanced textual analysis, this study bridges classical exegesis with contemporary issues, demonstrating the Quran’s enduring role in guiding ethical conduct in an era of changing relationship dynamics.